(untitled) (Al-Aasar, 2025)
The Islamic system of brotherhood aims to redistribute wealth from the affluent members of society in a legitimate manner to fulfill the social and economic needs of the poor and disabled, without distinction between Muslims and non-Muslims. A significant aspect of the life of the Holy Prophet (peace and blessings of Allah be upon him) is his emphasis on brotherhood, both within families and among society at large. However, biographers have often been reluctant to highlight this aspect in detail. A study of the Holy Prophet’s (peace and blessings of Allah be upon him) biography reveals his profound qualities of generosity, compassion, and concern for the rights and well-being of others. His system of brotherhood was universal, as he was sent as a mercy to all people. The teachings of the Prophet (peace and blessings of Allah be upon him) and the blessed hadiths underscore the importance of this system, making it a fundamental duty of an Islamic state. In contemporary times, Pakistan faces economic instability, with rising poverty and numerous crises, including natural disasters such as earthquakes and floods, which have caused widespread devastation. In such circumstances, there is an urgent need to establish a well-structured system of brotherhood to support the affected population. This study explores the guidance provided by the Seerat Tayyaba (peace be upon him) regarding social welfare and examines the responsibilities of both individuals and state officials in addressing these challenges effectively.